2011
DOI: 10.1097/aln.0b013e31823306f0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Curcumin in an Experimental Rat Model of Subarachnoid Hemorrhage

Abstract: Background: Subarachnoid hemorrhage (SAH) causes a high mortality rate and morbidity. It was suggested that oxidant stress plays an important role in neuronal injury after SAH. Therefore, we assessed the effect of curcumin on reducing cerebral vasospasm and neurologic injury in a SAH model in rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…models. 37,38) In accordance with previous studies, our results revealed that the reduction of GSH and SOD, but the elevation of MDA by Mn treatment in BV-2 cells. Of interest, these changes were significantly reversed by curcumin pretreatment (Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…models. 37,38) In accordance with previous studies, our results revealed that the reduction of GSH and SOD, but the elevation of MDA by Mn treatment in BV-2 cells. Of interest, these changes were significantly reversed by curcumin pretreatment (Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…2,21,27 It has long been known that glutamate is detrimental to neurons following SAH. 9,16,34 In an in vitro study, baicalein has been demonstrated to have a protective effect against glutamate-induced neurotoxicity. 17 In the present in vivo study, we also found that brain neurons can be protected against SAH though either direct attenuation of glutamate surge or by oxidative stress inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…16,34 In the sham group, the same procedure was performed, except normal saline was injected in place of blood. Mean rectal temperature was maintained at 37 ± 0.5°C with a heating pad.…”
Section: Induction Of Experimental Sah and Groupingmentioning
confidence: 99%
See 2 more Smart Citations